Happy High Performing Managers: Self-Sustaining Urban Myth or a Cause for Optimism? - Hosie, Peter; Willemyns, M.; Lehaney, B. (International Journal of Arts and Sciences, 2011)
A seminal question in human resource management is revisited by this investigation: ‘Do happy managers perform better than their discontented counterparts?’ This study provides support for the ‘happy-performing managers’ proposition by linking managers’ affective wellbeing and intrinsic job satisfaction with their contextual and task performance. The ‘happy-productive worker’ thesis has intrigued organisational researchers and practitioners for decades. Despite mixed empirical evidence from research, there is support in the literature and by practitioners for the notion that ‘a happy worker is a good worker’. A variation on the enduring debate of the happiness–productivity theme is presented, the ‘happy-performing managers’ proposition. An empirical study of Australian managers is reported to indicate which aspects of affective wellbeing predict their specific contextual and task performance.The emphasis was on investigating an aspect of human behaviour with the potential to enhance managerial performance. An empirical methodology was used to test the hypotheses and develop a Partial Model of Managers’ Affective Wellbeing, Intrinsic Job Satisfaction and Performance. Survey items were derived from the literature and administered to managers from Australian organizations using self–report on established affective wellbeing and intrinsic job satisfaction scales.